DEVELOPMENT OF SPEAKING COMPETENCE OF STUDENTS THROUGH QUICK SPEAKING IN PRIMARY CLASSES - Teshaboyev Dilmurod Rahmatjonovich; Madrakhimova Mahdiyabonu Khosiljon kizi (Western European Studies, 2024)
There are many ways to develop the pronunciation of students in educational processes, among them, the genre of rapid speaking of folk art plays an important role in the development of students' pronunciation. This article discusses the rapid pronunciations presented in elementary school textbooks and their importance in the development of the student's pronunciation
Keywords: Folklore; fast speaking; stress